Hypsometric Integral- Abasis for Determining the Erosion Status and Priority Numbers of Ungauged - Mishra, Narasingh (Journal of Soil and Water Conservation, 2022)
Hypsometic analysis is carried out to study the land forms of 20 selected watersheds of Upper Damodar Valley, Bihar. The hypsometrie integral for each watershed is evaluated and used to determine the erosion status and the priority numbers of each watersheds. These priority numbers are further compared with the observed priority numbers (by using SPR values).